Practical recommendations concerning prevention and correction of iron deficit in athletes - Vdovenko, N.V.; Ivanova, A.M.; Loshkarova, I.A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose : To develop practical recommendations for the prevention and correction of iron deficiency in athletes to improve the effectiveness of training and competitive activities, and accelerate recovery processes. Material: analysis and compilation of scientific and methodological literature on the exchange of iron, as well as ways of prevention and correction of iron deficiency in athletes. Results: It was found that iron deficiency in the body athletes may reduce sports (general and special) capacity and the situation of overtraining. The basic approaches on how to prevent and correct iron deficiency in athletes through nutrition. Conclusions: practical recommendations for the prevention and correction of iron deficiency in athletes.